2022
DOI: 10.1186/s12284-022-00577-1
|View full text |Cite
|
Sign up to set email alerts
|

The Long Read Transcriptome of Rice (Oryza sativa ssp. japonica var. Nipponbare) Reveals Novel Transcripts

Abstract: Background High-throughput next-generation sequencing technologies offer a powerful approach to characterizing the transcriptomes of plants. Long read sequencing has been shown to support the discovery of novel isoforms of transcripts. This approach enables the generation of full-length sequences revealing splice variants that may be important in regulating gene action. Investigation of the diversity of transcripts in the rice transcriptome including splice variants was conducted using PacBio l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Transcription-mediated gene fusion in plants was thought to be extremely rare for a long time. However, as the last decade unfolded, genome-wide surveys unveiled a multitude of transcription-induced chimeras [25][26][27]74]. Nevertheless, the functional and evolutionary potential, as well as the emergence of these fusion transcripts in plants, remains relatively uncharted territory.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Transcription-mediated gene fusion in plants was thought to be extremely rare for a long time. However, as the last decade unfolded, genome-wide surveys unveiled a multitude of transcription-induced chimeras [25][26][27]74]. Nevertheless, the functional and evolutionary potential, as well as the emergence of these fusion transcripts in plants, remains relatively uncharted territory.…”
Section: Discussionmentioning
confidence: 99%
“…in Oryza, it was estimated that fusion gene origination rates, contributing to the emergence of new genes, are notably high (63 fusion genes per species per million years) [24,30]. Another study conducted on rice reported that 6.8% of the total spliced isoforms were fusion transcripts [27]. Zhang et al identi ed that approximately 50% of novel genes on the short arm of chromosome 3 in rice have emerged through chimeric mechanisms [75].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, homology search was conducted with BLAST DIAMOND and proceeded with the BLAST2GO tool by utilising OmicsBox. The OmicsBox software allows for functional gene annotation utilities such as high throughput BLAST, Mapping, InterProScan, and Gene Ontology (GO) annotation [23,24].…”
Section: Ossce1 Gene Prediction and Annotationmentioning
confidence: 99%
“…This approach has been used to profile complex transcriptomes from neural tissues [2], tumor cells [3], T-cell receptors [4], and multiple plant tissues [5]. In addition, lrRNA-seq has been used to study allele-specific gene expression [6], circular RNAs [7], functional pseudogenes [8], and single-cell isoform diversity [9] [4].…”
Section: Introductionmentioning
confidence: 99%